From static to dynamic: modular architecture for oculo-palpebral prostheses with natural movement - Cardoso, Heitor Lara; Foggiatto, José Aguiomar; Stoppa, Marcelo Henrique; Ferreira, João Manoel Nascimento (Brazilian Journal of Production Engineering, 2026)
The absence of dynamic movement, especially the lack of synchronized eyelid blinking, represents a fundamental limitation in conventional ocular prostheses, contributing to The Uncanny Valley phenomenon and hindering social acceptance. Therefore, this study evaluated the feasibility of developing an accessible bio-inspired system capable of translating blink signals into a mechatronic device, while providing sufficient synchrony to enhance the perception of naturalness. This gap was addressed through the development of a real-time detection and actuation system. The architecture integrates non-invasive sensors attached to eyeglasses to capture the signal from the functional eye; a processing algorithm for event detection; and an actuator module to reproduce the movement on an animatronic platform. The tests validated the initial hypothesis, demonstrating a considerable degree of synchrony between the biological stimulus and the prosthetic response. The analysis of the resulting movement indicated natural kinematics, which proved effective in improving the perception of artificiality. This establishes a promising paradigm that transcends the purely aesthetic function of prostheses. By validating the integration of sensors, detection algorithms, and actuators, this research offers a significant contribution to the field of intelligent prosthetics, demonstrating a technically feasible solution for making them more expressive and socially integrated.
Keywords: Dynamic ocular prosthesis; modularity; assistive technology; blink detection; Uncanny Valley